15 Mbps underwater wireless optical communications based on acousto-optic modulator and NRZ-OOK modulation. (June 2022) - Wang, Tao; Wang, Bo; Liu, Liqi; Zhu, Renjiang; Wang, Lijie; Tong, Cunzhu; Song, Yanrong; Zhang, Peng
Highlights: A UWOC system based on acousto-optic modulator and NRZ-OOK modulation is verified. The highest data rate of 15 Mbps with 9 m distance and 1.53 × 10 -4 BER is obtained. Link distance of communication is up to 18 m with 12 Mbps data rate and 4.7 × 10 -3 BER. Influences of concentration on the attenuation coefficient and BER are investigated. Abstract: Communications with link distance of hundreds of meters and data rate of tens of Mbps are highly demanded in underwater wireless optical communications (UWOC) between autonomous underwater vehicles (AUVs) and submarines, or among others underwater platforms. In these cases, a high-power light source has to be used and an external modulation must be imposed. Here we present an UWOC system based on acousto-optic modulator (AOM), Non-Return-to-Zero On-Off Keying (NRZ-OOK) modulation and 520 nm green laser diode light source. A data rate of 15 Mbps, the highest reported values of an UWOC system using AOM to our best knowledge, with 9 m distance and 1.53 × 10 -4 bit error rate (BER), as well as the longest distance of 18 m with 12 Mbps data rate and 4.7 × 10 -3 BER are obtained in the tap water, in which an attenuation coefficient of 0.0503 m −1 for 520 nm wavelength is measured. By adding different dosages of Maalox suspension, different types of water quality are prepared, and the influences of Maalox concentration on the attenuation coefficient and the BER are investigated. It is found that increasing Maalox concentrations would worse the scatter effect of light beam, which further affect the transmission performance of the signal.